THE IMPACT OF PSAK 115 (REVENUE RECOGNITION) AND PSAK 116 (LEASES) ON EARNINGS MANAGEMENT - Febriyanty, Kartika Setya; Andayani, Wuryan (Jurnal Akuntansi dan Keuangan Indonesia, 2026)
Background: Earnings management remains a persistent issue due to managerial discretion in accounting standards. To enhance transparency, Indonesia adopted PSAK 115 Revenue from Contracts with Customers and PSAK 116 Leases in 2020. However, empirical evidence regarding their impact on earnings management remains mixed. Method: This study uses secondary data from technology and telecommunications, real estate, and construction companies listed on the Indonesia Stock Exchange (2018–2021). The implementation of PSAK 115 and PSAK 116 is measured using dummy variables, while earnings management is proxied by discretionary accruals. Findings: The results show that PSAK 115 has a negative effect on earnings management. This finding supports previous studies by Napier and Stadler (2020) and Lee and Choi (2024) in the context of Indonesian companies. In contrast, PSAK 116 shows no significant effect on earnings management. Additional testing is conducted and produces consistent results. Conclusion: New revenue recognition standards are more effective in limiting earnings management while new lease recognition standards have no effect on limiting accrual-based earnings management. Novelty/Originality: This study simultaneously examines PSAK 115 and PSAK 116 and distinguishes between lessees and lessors, providing a more comprehensive perspective on accounting standards and earnings management.